Polymorphism in 1-methylhydantoin: investigation by periodic DFT calculations and characterization of the third polymorph. Issue 38 (14th September 2020) - Nogueira, Bernardo A.; Milani, Alberto; O. Ildiz, Gulce; Paixão, José A.; Castiglioni, Chiara; Fausto, Rui
Abstract : In previous studies, two different polymorphs of 1-methylhydantoin were identified (forms I and II ) and characterized using infrared and Raman spectroscopies, and X-ray diffraction. In this work, a new polymorph of the compound (III ) is described. Abstract : In previous studies [Puszyńska-Tuszkanow et al. Polyhedron, 2011, 30 (12), 2016; Nogueira et al. J. Phys. Chem. A, 2014, 118 (31), 5994; Nogueira et al., J. Mol. Struct., 2017, 1148, 111], two different polymorphs of 1-methylhydantoin (1-MH, C4 H6 N2 O2 ) were identified (forms I and II ) and characterized using infrared and Raman spectroscopies, as well as by X-ray diffraction. In this work, a new polymorph of the compound (form III ) is described. The new polymorph was characterized spectroscopically and its structure was determined for the first time by single crystal X-ray diffraction. Very interestingly, the crystal of polymorph III was found to exhibit a high- Z ′ ( Z ′ = 3) asymmetric unit and 12 molecules in the unit cell ( Z = 12), which contrasts with the simpler crystal structures found previously for forms I and II ( Z = 4; Z ′ = 1). Besides, a thorough study of the polymorphism of 1-MH was performed with the help of state-of-the-art first principles fully periodic calculations of the structure, as well as infrared and Raman spectra of the different polymorphs of the compound. Marker-bands in the infrared and Raman spectra of the polymorphs are proposed for fast spectroscopic identification of the polymorphs.